A comparative assessment of the physicochemical parameters and phytoplankton assemblages in San Joaquin River and Bariw River in Palo, Leyte - Campo, Raymond G.
The San Joaquin River is a major river system in Palo, Leyte draining to San Pedro Bay. In contrast, Bariw River is smaller in size and is a tributary of the San Joaquin River. Differences in physical factors, such as sand mining and riparian use are observable between the two rivers. The study aims to evaluate the physicochemical parameters and the phytoplankton components of both rivers. The study also aims to know if there is a correlation between each physicochemical parameter and the phytoplankton assemblages found in both rivers. Water samples from 1 meter below the surface were taken from both rivers in November 2008 and January 2009. The structure of the phytoplankton community and physicochemical parameters were evaluated. Cluster analysis revealed that all the stations of both rivers are homogenous with regard to the physicochemical parameters that were measured. A total of 33 phytoplankton taxa were identified in all stations of the two rivers. Phytoplankton composition and cell densities did not significantly differ between the two rivers. Diatoms, such as Nitzschia, Navicula, Leptocylindricus, and Coscinodiscus were dominant in sampling stations, except at the headwater, where Trachelomonas was dominant. Therefore, the two rivers are similar and may be classified under a single system based on their physicochemical features.